Leveraging Blue Ocean Strategy: Cutting-Edge Approaches to Cafe Management Development - Ningrum, Laila Dwi; Yafiz, Muhammad; Harahap, Muhammad Ikhsan (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
In an increasingly competitive cafe market, innovation as a primary strategy is crucial to enhancing competitiveness and business growth in Tanjung Morawa. However, the challenges of effectively implementing innovation in cafe management may hinder cafes' ability to adapt to changing market trends and fluctuating consumer preferences quickly. Therefore, this research explores the role of innovation as a survival strategy in cafe management in Tanjung Morawa. Using the Blue Ocean Strategy approach, the study analyzes how innovation can enable cafes to create or redefine markets by offering unique value propositions and distinguishing themselves from competitors. The research methodology is descriptive qualitative, utilizing primary and secondary data sources, including surveys, interviews, documentation, and data analysis. Key informants include the owners of Skala Coffee, Cafe Abah Awak, and Selow Time Coffee. Data analysis techniques involve data reduction, presentation, and conclusion drawing. Findings demonstrate that innovation plays a crucial role in enhancing cafe competitiveness, with factors such as monitoring market trends, flexibility in responding to change, product quality, pricing, service delivery, and customer experience identified as keys to success. The practical implication of this research is that cafe owners must continue to foster innovation as part of their survival strategy in a competitive market environment.